Decomposing the Gender Pay Gap in the Australian Managerial Labour Market - Watson, I (My University, 2010)
This article examines the gender pay gap among full-time managers in Australia over the period 2001 to 2008. Using decompositions I explore the issue of discrimination, as well as the roles played by labour force experience and parenting. The results show that female managers earned on average about 27 per cent less than their male counterparts and the decompositions suggest that somewhere between 65 and 90 per cent of this earnings gap cannot be explained by recourse to a large range of demographic and labour market variables. A major part of the earnings gap is simply due to women managers being female. In addition, the presence of dependent children worsens the earnings gap, while the financial returns to labour force experience diminish in the latter years among female managers rather than stabilising, as they do for male managers. Despite the characteristics of male and female managers being remarkably similar, their earnings are very different, suggesting that discrimination plays an important role in this outcome. The article uses eight waves of HILDA data to fit mixed-effects models which are then used for Blinder-Oaxaca decompositions. In addition, a recent simulated change approach, developed by Olsen and Walby in the UK, is also implemented using this Australian data.
Keywords: Employment; Income & Finance -- Income inequality; Gender -- Gender differences; Disadvantage -- Discrimination; Income & Finance -- Wage gap; Labour market; Income, wealth and finances; Gender; Employment; Income & Finance; Disadvantage; Gender; Discrimination; Gender differences; Income inequality; Wage gap; Income, wealth and finances; Employment and unemployment; Gender